Associations between weight talk exposure and unhealthy weight control behaviors among young adults: A person-centered approach to examining how much the source and type of weight talk matters. (March 2021) - Simone, Melissa; Hazzard, Vivienne M.; Berge, Jerica M.; Larson, Nicole; Neumark-Sztainer, Dianne
Highlights: Weight talk exposure is pervasive among young adults. Weight talk is associated with higher rates of unhealthy weight control behaviors. Men and women were exposed to parental and peer weight talk to varying degrees. The association between weight talk and unhealthy weight control differed by gender. Abstract: This study characterized common patterns of weight talk and examined associations with unhealthy weight control behaviors (UWCBs) in young adults. Participants (n = 1298) were from EAT 2018 (Eating and Activity Over Time), a population-based study of emerging adults (mean age = 22.2; 53.6 % women). Latent class analyses (LCA) derived classes based on weight talk exposure for men and women. Generalized linear models examined the association between weight talk classes and extreme/less extreme UWCBs. LCA results revealed 4 patterns of weight talk exposure among young adult women: minimal weight talk (38.8 %), peer weight talk (35.2 %), multi-source weight talk (13.5 %), and parental weight talk (12.6 %). Three classes emerged among men: minimal weight talk (44.0 %), peer weight talk (29.7 %), and multi-source weight talk (26.3 %). Among young adult women, the parental weight talk class reported the highest levels of extreme and less extreme UWCBs. Among young adult men, the multi-source weight talk class reported the highest levels of less extreme UWCBs. Results provide evidence regarding the importance of parental weight talk, even among young adult children, whether or not parental weight talk is accompanied by peer weight talk. Parents have the potential to improve their young adults' weight-related behaviors through avoiding weight talk.